Trends in Seasonal Sea Ice Duration in Southwestern Hudson Bay - Gough, William A.; Cornwell, Adam R.; Tsuji, Leonard J.S. (ARCTIC, 2004)
The southwestern region of Hudson Bay is one of the last areas in the Hudson and James Bay lowlands region to become free of sea ice in the spring. This late breakup is due to the effects of winds and currents. By analyzing time series with three different statistical techniques, we found a statistically significant increase in the length of the ice-free season in this region from 1971 to 2003. Much of this increase was attributed to earlier breakup of the ice, which is consistent with increased spring temperatures in this region. The onset of breakup advanced by at least three days per decade over the study period. La partie sud-ouest de la baie d'Hudson est l'une des dernières zones des basses terres de cette baie et de la baie James à se libérer de la banquise au printemps. Cette débâcle tardive est due aux effets des vents et des courants. En analysant des séries chronologiques à l'aide de trois techniques statistiques différentes, on a découvert que, de 1971 à 2003, la région a connu une augmentation sensible dans la durée de la saison d'eau libre. Une grande partie de cette augmentation a été attribuée à une débâcle précoce, ce qui va de pair avec une hausse des températures printanières dans la région. Le début de la débâcle a avancé d'au moins trois jours par décennie au cours de la période d'étude.